2006
DOI: 10.1017/s1047951106000126
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide survey of pregnancy and delivery in patients with coronary arterial lesions caused by Kawasaki disease in Japan

Abstract: The results of pregnancy and delivery were favourable. The mode of delivery should be primarily determined by obstetrical considerations, rather than the coronary arterial lesions caused by Kawasaki disease. Excessive anticoagulant therapy may not be needed for this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 21 publications
1
20
0
2
Order By: Relevance
“…382 A study in Japan of 46 pregnancies in 30 women also showed no cardiac events. 383,384 Catheter and Surgical Coronary Artery Interventions…”
Section: Reproductive Counselingmentioning
confidence: 99%
“…382 A study in Japan of 46 pregnancies in 30 women also showed no cardiac events. 383,384 Catheter and Surgical Coronary Artery Interventions…”
Section: Reproductive Counselingmentioning
confidence: 99%
“…After the appearance of several case reports, 146 -149 the results of a Japanese nationwide survey on the current status of pregnancy and delivery in patients with coronary aneurysm or stenosis have been reported recently. 150 Among 46 deliveries of 30 patients identified, there were no cardiac events irrespective of the mode of delivery (vaginal or cesarean) or the use of anticoagulation therapy (aspirin or heparin). However, these data do not provide any definitive information on this issue, and future prospective trials need to address the appropriate management of this population.…”
Section: Follow-up and Future Recommendationsmentioning
confidence: 99%
“…La aterectomía rotacional es el procedimiento de elección en los aneurismas calcificados que tienen lesiones estenóticas, aunque la experiencia en [70][71][72] (clase de recomendación II a, nivel de evidencia C).…”
Section: Intervenciones De Las Coronarias: Angioplastía Y Cirugía De unclassified